The Impact of Hospital Management Information System (HMIS) on Work Efficiency of Laboratory Services - Djusran, Ilyas; I.G.P. Agus Ferry Sutrisna Putra; Putu Gede Subhaktiyasa; Anak Agung Ayu Eka Cahyani (Jurnal Kesehatan Cendikia Jenius, 2025)
Hospitals as public service providers are required to optimize information technology through the Hospital Management Information System (HMIS) to improve the quality and efficiency of health services, including laboratory installations. However, HMIS implementation often faces technical and coordination barriers between units that may reduce its effectiveness. This study aimed to analyze the effect of HMIS on the work efficiency of laboratory personnel at Kendari City Hospital. This research applied a quantitative approach with a cross-sectional design. All laboratory staff (medical laboratory technologists, nurses, and specialist doctors) totaling 28 respondents were selected using total sampling. Data collection was conducted from February to July 2025 using a valid and reliable Likert-scale questionnaire, and analyzed using simple linear regression and one-tailed t-tests with SPSS version 27. The results showed that most respondents had positive perceptions of HMIS implementation (mean 4.19) and work efficiency (mean 4.28). Regression analysis revealed a significant positive effect of HMIS on work efficiency (coefficient 0.657; R² 0.331; t-statistic 3.590 > t-table 1.706). In conclusion, HMIS implementation positively influences laboratory personnel work efficiency. Continuous development and evaluation of HMIS, as well as integration with the Laboratory Information System, are recommended to enhance laboratory service quality.